A comparison of the epidemiology of ice hockey injuries between male and female youth in Canada. Issue 8 (1st October 2014) - Forward, Karen E; Seabrook, Jamie A; Lynch, Tim; Lim, Rodrick; Poonai, Naveen; Sangha, Gurinder S
Abstract: BACKGROUND: Hockey is played by youth across Canada, and its popularity has increased dramatically among females in the past decade. Despite this, there has been little epidemiological research comparing the injury patterns of young female and male hockey players. OBJECTIVE: To describe and compare injuries sustained by female and male youth hockey players using the Canadian Hospitals Injury Reporting and Prevention Program database. METHODS: In the present cross-sectional, retrospective comparison study, the Canadian Hospitals Injury Reporting and Prevention Program database was used to identify all hockey-related injuries sustained by children seven to 17.5 years of age over a 15-year period (January 1995 to December 2009). Exclusion criteria included paid professional players and children with injuries sustained while playing road hockey. RESULTS: Inclusion criteria were met by 33, 233 children (2637 [7.9%] females and 30, 596 [92.1%] males). Compared with males, females reported proportionately more soft tissue injuries (39.8% versus 32.6%; P<0.01) and sprains/strains (21.1% versus 17.6%; P<0.01). Males experienced more fractures (27.1% versus 18.2%; P<0.01) and were most often injured through body checking (42.8% versus 25.7%; P<0.01). Females showed a trend toward increased concussion with age, and were most often injured through collisions (28.6% versus 24.6%; P<0.01). CONCLUSION: Compared with males, female hockey players sustained proportionately more soft tissue injures and sprains/strains, and showed a trend toward concussions in late adolecence. Males experienced more fractures, shoulder injuries and injuries due to body checking. Further research is required to identify risk factors for injury in female youth hockey players and to target injury prevention.